Maintaining effective engineering leadership a new dependence on effective process - Morrison, Raymond (The Institution of Engineering and Technology, 2013)
The book comprises of 8 chapters dealing with the following subjects: engineering leadership; process engineering; process-oriented organisation; product vigilance; financial impact and change management.